Comparative Clinical and CBCT Assessment of the Efficacy of Autologus Bone Block Graft Block Graft versus Resective Osseous Surgery and Open Flap Debridement in management of Hemiseptal Periodontal Defects: A Pilot Study - Dr. Vaibhav Tiwari; Dr. Prasad V Dhadse (The Bioscan, 2026)
Aim: The present study aimed to comparatively evaluate autogenous bone graft (ABG), resective osseous surgery (ROS), and open flap debridement (OFD) in the treatment of hemiseptal periodontal defects.